Design of gravimetric primary standards for field-testing of hydrogen refuelling stations. (June 2020) - de Huu, M.; Tschannen, M.; Bissig, H.; Stadelmann, P.; Büker, O.; MacDonald, M.; Maury, R.; Neuvonen, P.T.; Petter, H.T.; Rasmussen, K.
Abstract: The Federal Institute of Metrology METAS developed a Hydrogen Field Test Standard (HFTS) that can be used for field verification and calibration of hydrogen refuelling stations. The testing method is based on the gravimetric principle. The experimental design of the HFTS as well as the description of the method are presented here. The HFTS has been tested at METAS with nitrogen gas at −40 °C to mimic a refuelling process in the field. Laboratory tests have shown that icing on the pipes of the HFTS have a non-negligible impact on the results. Field-testing with the HFTS has also been performed at the Empa hydrogen refuelling station with hydrogen at up to 70 MPa. The major uncertainty components have been identified and assigned values. The required expanded uncertainty of 0.3% could be achieved. A detailed uncertainty budget has been presented and shows that the scale is the largest contributor; buoyancy corrections only play a minor role. For the lowest uncertainty measurements, appropriate waiting times or cleaning methods to get rid of icing are required. Highlights: Description of a field testing standard based on the gravimetric principle for calibrating and testing hydrogen refuelling stations. Detailed description of the measurement method with corrections. Experimental results under laboratory conditions and under field conditions at a hydrogen dispenser. Detailed uncertainty budget for the gravimetric measurement.